Magnetic properties and nanocrystallization behavior of Co-based amorphous alloy - Nykyruy, Yu.; Mudry, S.; Kulyk, Yu.; Prunitsa, V.; Borysiuk, A. (Physics and Chemistry of Solid State, 2023)
The magnetic properties of the amorphous Co57Fe5Ni10Si11B17 alloy have been studied by a vibrating sample magnetometer. The temperature dependence of saturation magnetization was measured and the Curie point and crystallization onset temperature were determined as 560 K and 760 K respectively. The coercive force was obtained as 200 A/m and saturation magnetization - 65 Am2 /kg. The alloy was produced in the form of a ribbon thickness of 30 µm using the melt spinning method, and its internal amorphous structure was examined by the X-ray diffraction method. The crystallization behavior of the alloy was studied using series of isothermal annealing of the samples of the alloy at temperatures in the range of 723-1023 K for different exposures (up to 240 minutes) and nanocrystalline phases were detected by the X-ray diffraction analysis.